Rethinking Indonesian Single-Member Companies: Lessons from the European Union for Sustainable Business Governance - Abbas, Ilham; Ramadani, Rizki; Aswari, Aan; Yaqien Makkarateng, Ma'adul (Jambe Law Journal, 2026)
The introduction of the Indonesian Perseroan Perseorangan (Single-Member Company/SMC) under the Job Creation Law is intended to improve the ease of doing business. Allowing a company to be established and managed by a single individual, the SMC signifies a transformation from traditional corporate law principles. While existing studies emphasize economic deregulation and business formalization, limited attention has been paid to whether this simplified corporate model is compatible with the emerging paradigm of Sustainable Corporate Governance (SCG). This study addresses that gap by evaluating the Indonesian SMC framework through an SCG perspective and comparing it with the European Union’s regulatory approach. Its principal contribution is the development of an SCG-based comparative evaluative framework for assessing simplified corporate entities, demonstrating that the compatibility of Single-Member Company regimes should be measured not only by ease of doing business but also by their capacity to ensure long-term governance accountability, stakeholder protection, and environmental responsibility. Employing normative legal research and a comparative legal approach, this study examines Indonesia's regulatory framework in comparison with the European Union's SMC regime using four dimensions of SCG: governance accountability, transparency and sustainability disclosure, stakeholder and creditor protection, and corporate environmental responsibility. The findings reveal that although Indonesia's regulatory model significantly improves business accessibility and administrative efficiency, it provides limited institutional safeguards to support sustainable governance. By contrast, the European Union adopts a more balanced regulatory approach that combines business flexibility with governance safeguards. Therefore, the study proposes a proportionate governance model capable of reconciling business simplification with sustainable corporate governance.